Coding in the real world - Lyons, Heather (Heather K.); Westgate, Alex; Crisp, Dan (2018)
Did you know that computers are around us almost all the time? They're in cars, streetlights, and even the grocery store checkout! Learn all about the computers that help us every day and the computer code that makes them work. Then, using the link in this book, you can try out your new skills and design your own helpful machines!
Everyday computers -- Follow that robot -- Road safety -- Car or computer -- Home sweet home -- Flying high -- Shopping -- Money, money -- The future.
Includes index.
6-10
Keywords: Computer programming -- Juvenile literature; Information technology -- Juvenile literature; Technological innovations -- Juvenile literature